Very low computational complexity (VLCC) architecture for optical interconnect in data center networks. (20th December 2017) - Fayyaz, Mohsin; Aziz, Khurram; Mujtaba, Ghulam; Fayyaz, Ahmad; Khan, Samee U.
Summary: Real time cloud computing applications require a low latency network. The latency of optical interconnect in Data Center Networks (DCNs) is dependent on the complexity of the routing algorithm. The routing algorithm makes decisions about the forwarding of a packet on each successive node. If a routing algorithm is more complex, it requires more hardware resources to implement, which incurs extra cost and latency to the optical interconnect. This paper analyzes the complexity of existing architectures for the first time by showing Big O notation of complexity for each architecture. Different factors affecting the computational complexity of any routing algorithm are identified. This paper proposes a new architecture named VLCC. It has very low fixed routing complexity irrespective of network size. It has no packet loss at the network layer under many to many and all to one communication pattern. The only packet loss is at the physical layer due to signal degradation caused by optical components. The level of signal degradation is analyzed in terms of received signal power, bit error rate (BER), receiver sensitivity, path loss, and blocking probability. VLCC architecture is highly suitable for real time applications that require deterministic quality of service (QoS), where network performance is not affected by the traffic pattern.